2015
DOI: 10.1080/19443994.2014.942704
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity removal from aqueous environments by Pistacia atlantica (Baneh) seed extract as a natural organic coagulant aid

Abstract: A B S T R A C TCoagulation/flocculation, as an important step in water treatment processes, is applied for turbidity removal of raw water coming from suspended particles and colloidal material. In this study, the ability of Pistacia atlantica seed extract, as a natural organic coagulant aid along with ferric chloride for turbidity removal from synthetic solutions, was investigated. Coagulation ability of this coagulant was assessed by the use of standard jar test measurement. The influence of several operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…These proteins involve in charge neutralization and adsorption of a colloidal particle in water. Bodlund [28] has demonstrated that protein content in coagulant active extract influences the coagulation process during turbidity removal. It is known that -active coagulant extract from fruit seed acts as a coagulating agent which is non-ionic and involves in coagulation mechanisms.…”
Section: Functional Groups Present In Active Coagulant Extract Solution From Tropical Fruit Seedsmentioning
confidence: 99%
“…These proteins involve in charge neutralization and adsorption of a colloidal particle in water. Bodlund [28] has demonstrated that protein content in coagulant active extract influences the coagulation process during turbidity removal. It is known that -active coagulant extract from fruit seed acts as a coagulating agent which is non-ionic and involves in coagulation mechanisms.…”
Section: Functional Groups Present In Active Coagulant Extract Solution From Tropical Fruit Seedsmentioning
confidence: 99%
“…Se ha reportado la remoción de caolín mediante extractos de semillas de Pistacia atlantica (Bazrafshan, Mostafapour, Ahmadabadi, & Mahvi, 2015). Efluentes contaminados con colorantes para pinturas acrílicas se han decolorado con la adición de Cactus opuntia (ficus-indica) con un 94% de eficiencia en la remoción del color, demanda química de oxígeno y turbidez (Vishali & Karthikeyan, 2015).…”
Section: Coagulantes Naturalesunclassified
“…Según resultados experimentales, a pH ácido, entre 1 y 6, la remoción de turbidez fue entre 79,4 y 92,1%, pero a pH básico, entre 10 y 12,5, la remoción fue entre 81,6 y 99,2%. Según el grado de compactación y estabilidad mecánica, a valores de pH básicos se obtiene la mejor calidad del lodo residual (Bazrafshan et al, 2015). contaminación coloidal, por tanto los extractos de guarango disponen de un carácter electropositivo en la desestabilización coloidal, de acuerdo con los mecanismos de neutralización de cargas.…”
Section: Mecanismos Físico-químicos De Coagulación Naturalunclassified
“…However, there are some disadvantages induced by using chemical coagulants such as relatively high costs, low-effectiveness at low temperature, production of large volume of sludge, affect the treated water pH, and adverse effects on human health (Bazrafshan et al 2015;de Oliveira Cardoso Nascimento et al 2021). Furthermore, the resulting elevated concentration of aluminum residuals in water are linked with neurodegenerative diseases such as Alzheimer's, as well as neurotoxic and carcinogenic effects (Rondeau et al 2000;Huang et al 2015).…”
Section: Introductionmentioning
confidence: 99%